Assessing the effects of virtual reality-based positive psychotherapy on emotion, life satisfaction, and suicidal ideation in major depression: A mixed-methods randomized controlled trial - Fahimeh Alsadat Hosseini; Kimia Bahman; Maryam Shaygan; Shahrazad Yektatalab (PLoS ONE, 2026)
Background Positive psychotherapy (PPT) targets the enhancement of well‑being in individuals with major depressive disorder (MDD), and virtual reality (VR) offers an immersive medium for delivering such experiential interventions. However, most VR-based approaches for depression are grounded in cognitive‑behavioral frameworks, leaving the application of PPT within VR environments largely unexplored. This study examined the effects of VR-based PPT on emotional experiences, life satisfaction, and suicidal ideation in individuals with MDD. Methods In this sequential explanatory mixed‑methods study, 78 patients were randomly assigned to VR-based positive psychotherapy (intervention; n = 39) or an equivalent face-to-face format (control; n = 39). Both groups received three sessions of positive psychotherapy, differing only in delivery mode. The quantitative phase assessed changes in affect, life satisfaction, and suicidal cognitions before and after each session using the PANAS, SWLS, and B-SCS. A subsequent qualitative analysis of the intervention group was conducted to contextualize and further interpret the quantitative findings. Results The results demonstrated a significant multivariate effect over time (Wilks’ Lambda = 0.316, F(20,57) = 6.176, ɳ² = 0.684, P < 0.001), indicating significant improvements in the outcome measures across sessions. Within‑group effect sizes ranged from small to moderate (d = 0.02–0.53), with comparable improvements observed in both the VR-supported and face-to-face formats. Qualitative findings further enriched the interpretation of these patterns, yielding two overarching themes: “user-friendly program” and “efficient psychotherapy program.” Conclusion Both VR-based and face-to-face positive psychotherapy were associated with improvements in emotional experiences, life satisfaction, and suicidal ideation in individuals with major depressive disorder. VR-based delivery appeared feasible and acceptable, with outcomes comparable to the traditional face-to-face format in this preliminary trial. Further studies with larger samples and longer follow-up are needed to confirm these findings and clarify their clinical implications. Trial registration: This trial was prospectively registered in the Iranian Registry of Clinical Trials (IRCT20201001048893N7, registration date: 16 November 2022, URL: https://irct.behdasht.gov.ir/trial/66424 ) prior to the enrollment of the first participant.